The effect of enterprise risk management on prevention and detection fraud in Indonesia's local government - Tarjo Tarjo; Henryan Vishnu Vidyantha; Alexander Anggono; Rita Yuliana; Musyarofah (Cogent Economics & Finance, 2022)
It may sound familiar to use Enterprise Risk Management (ERM) to prevent and identify fraud. However, the use of this well-known strategy in municipal administration is still uncommon. Fraud is a major concern in local government fiscal management. We acquired 151 data points from the Supervisory Apparatus of Local Government Agencies in Indonesia using a questionnaire. To test the hypothesis, this study employs regression analysis. According to the findings, the control environment, risk assessment, control activities, information and communication, and monitoring all have a significant impact on fraud prevention and detection. This work contributes empirically to the use of Enterprises Risk Management to minimize and identify fraud in Indonesian local governments.
Keywords: 330; Enterprise risk management; Indonesia local government; fraud prevention anddetection